Experimental Comparison of Fiducial Markers Used in Proton Therapy: Study of Different Imaging Modalities and Proton Fluence Perturbations Measured With CMOS Pixel Sensors - Reidel, Claire-Anne; Horst, Felix; Schuy, Christoph; Jäkel, Oliver; Ecker, Swantje; Henkner, Katrin; Brons, Stephan; Durante, Marco; Weber, Uli (Frontiers in Oncology, 2022)
Fiducial markers are used for image guidance to verify the correct positioning of the target for the case of tumors that can suffer interfractional motion during proton therapy. The markers should be visible on daily imaging, but at the same time, they should produce minimal streak artifacts in the CT scans for treatment planning and induce only slight dose perturbations during particle therapy. In this work, these three criteria were experimentally investigated at the Heidelberg Ion Beam Therapy Center. Several small fiducial markers with different geometries and materials (gold, platinum and carbon-coated ZrO2) were evaluated. The streak artifacts on treatment planning CT were measured with and without iMAR correction, showing significantly smaller artifacts from markers lighter than 6 mg and a clear improvement with iMAR correction. Daily imaging as X-ray projections and in-room mobile CT were also performed. Markers heavier than 6 mg showed a better contrast in the X-ray projections, whereas, on the images from the in-room mobile CT, all markers were clearly visible. In the other part of this work, fluence perturbations of proton beams were measured for the same markers by using a tracker system of several high spatial resolution CMOS pixel sensors. The measurements were performed for single energy beams, as well as for a spread-out Bragg peak. Three dimensional fluence distributions were computed after reconstructing all particle trajectories. These measurements clearly showed that the ZrO2 markers and the low-mass gold/platinum markers (0.35 mm diameter) induce perturbations being 2-3 times lower than the heavier gold or platinum markers of 0.5 mm diameter. Monte Carlo simulations, using the FLUKA code, were used to compute dose distributions and showed good agreement with the experimental data after adjusting the phase space of the simulated proton beam compared to the experimental beam.